Evaluation and optimization of DNA extraction method from plant species leaf for polymerase chain reaction analysis - Zulaikha, binti Zainal (Universiti Malaysia Sarawak (UNIMAS), 2012)
DNA extraction in plant genetic studies is essential components for understanding molecular study and biology applications. Genomic DNA was extracted from 5 different selected plant species which are Capsicum annuum L.. Curcuma longa L .• lasminum officinale L.. Carica papaya L., and PsophocalplIS tetragonolobus L. by using two DNA extraction protocols which are CTAB extraction method and protocols without using liquid nitrogen. Leaves were fixed in different fixing solutions containing absolute alcohol (99.9%), chloroform and EDT A, without liquid nitrogen. DNA quality and quantity obtained were comparable to those isolated with liquid nitrogen which used in breaking the cell wall. As a result, the DNA concentration in the A260/280 ratio with liquid nitrogen was in range l.9-2.15 and with fixing solutions was 1.1-l.9. Good quality DNA from fresh leaf was obtained without using liquid nitrogen and was successfully amplified by polymerase chain reaction using OPDF-8 primer. The same protocols also can be useful for extracting high molecular weight DNA from other plant materials containing large amounts of secondary metabolites and essential oils.